Maintenance for ice skating rink at Sunway Pyramid / Nurfirdawati Muhamad Hanafi - Muhamad Hanafi, Nurfirdawati (2001)
Ice skating rink is becoming more and more popular indoor activities or sport in Malaysia. Since the opening of Ice Pyramid which is located in the Sunway Pyramid shopping complex, eventually, more ice skating rinks have been opened to the public. Ice pyramid, is one of the largest and best ice skating rink in Malaysia Due to rapid technology development, nowadays, ice rink can either be made of ice slab or artificial slab, which comes in a selection of material, from polypropylene, polyethylene or fluorinated polyethylene. However, in Malaysia, such artificial technology hasn’t been adopted yet. Ice rink is an example of nature’s gift, which is adept commercially. Before this, ice was another meant of transporation on the frozen waterways and was only available in colder countries. Due to changes in technology, researchers have found a way on how to adopt this invention without giving detail particular on the existing climatic condition of the country or place. Maintenance for Ice Skating Rink at Sunway Pyramid The rink technology, characteristics and logistics as well as the rink maintenance are somewhat different from other sport activity complex. This is due to the invention needs daily and planned maintenance program to get the operation running continuously.